Optimization of ionic liquid-based microwave-assisted extraction on brazilin levels from sappan wood and its dipeptidyl peptidase IV inhibition activity - Islamudin Ahmad, Erwi Putri Setyaningsih, Ayun Erwina Arifianti, Fadlina Chany Saputri, Abdul Mun’im (Journal of Applied Pharmaceutical Science, 2021)
To elevate brazilin levels from sappan wood (Caesalpinia sappan) using the optimized ionic liquid-based microwave-assisted extraction (IL-MAE) method and to evaluate its dipeptidyl peptidase IV (DPP-IV) inhibition activity. According to the preoptimization results, the IL-MAE method condition’s optimization was carried out using response surface methodology with the Box–Behnken design. Brazilin levels were determined by the high performance liquid chromatography (HPLC) gradient method (0.3% acetic acid in water and acetonitrile). A DPP-IV inhibition activity assay was then conducted using the DPP-IV-GloTM kit and determined using Glomax (Promega, Madison, WI) with an excitation of 350–360 nm and an emission of 450–465 nm. The most optimized extraction condition was 1.5 mol/l 1-butyl-3-methyl imidazolium bromide ([BMIM]Br), 1:20 g/ml solid-to-liquid ratio, and 9 minutes of extraction time. HPLC analysis of sappan extract showed brazilin levels of 807.56–948.12 mg/g extract. Sappan extract gives the in vitro inhibitory value of DPP-IV activity of >90%. The inhibition concentration of 50% value was obtained including 9.37 µg/ml (sitagliptin), 11.7 µg/ml (brazilin standard), 16.35 µg/ml (extract sample), and 22.15 µg/ml (tannin removal sample). In the present study, imidazolium basic IL-MAE was optimized and first applied to elevate the brazilin levels from sappan wood. Thus, this is an optimum extraction condition for elevating sappan wood’s brazilin levels rapidly, efficiently, quickly, and environmentally friendly.
Keywords: Brazilin, dipeptidyl peptidase IV, ionic liquidbased microwave-assisted extraction, response surface methodology, sappan wood (Caesalpinia sappan).